295. A 3T MRS in the analysis of cell differentiation induced in human Neuroblastoma cells treated with l-Acetylaspartate and electro stimulation. (December 2018) - Fratello, A.; Caivano, R.; Di Costanzo, F.; Mazzoccoli, C.; Cammarota, A.; Gallo, C.; Piccoli, C.
Abstract : Purpose: A 1 H-MRS spectrum on a patient's healthy brain differs on the pathological part of the same organ. L-Acetylaspartate (NAA), due to its high concentration in the brain, returns intense MRS spectrum signal, reducing its intensity more or less drastically in patients suffering from various brain diseases. Even cultures of brain cells have the same spectrum as man. Because brain cells function with specific electrical impulses, we electrically stimulated the brain cells of a tumour, in the presence of NAA, to attempt to modify their MRS spectrum from pathological to normal. Methods: Hodgkin and Huxley (1963) have experimentally documented on the cellular membrane a ddp (ΔV) of −90 mV. The whole human organism starting from the cells to organs and apparatus behaves like a more or less complex system of RLC circuits. The T.H. Bullock (1959) defines three different types of electrical potentials: pacemaker; transduction; action. When electrical impulse crossing the cell's RC circuit are modified if the cell has low resistance ( norm-functional) or high resistance (pathology). These have suggested the idea to compensate, in the pathological tissue, a well-defined molar doses of the NAA. TENS has shown, on humans, that the square shape of the signal is physiologically the most advantageous for several reasons. The research was carried out on human Neuroblastoma cells, provided by the University Hospital of MANASSAS (Virginia) for research purposes only. The human cell cultures of Neuroblastoma were placed on multiwall plates with a cell culture medium substrate. The procedure, on three sets of plates with the same characteristics, is divided into three phases: 1st PHASE: suitable molar concentration of L-Acetylaspartate (NAA); 2nd PHASE: cell plates treated with NAA, concentration of 4 mM, untreated cell plates (controls) received electro stimulation with different times (20, 40, 60 min); 3rd PHASE: An equal number of plates, treated and not with NAA, were not electro stimulated. The plates had cells, cells treated with NAA, culture medium, culture medium and NAA. All samples underwent nuclear magnetic resonance spectroscopy. Preliminary results: The spectra, after the different electro stimulations, were acquired at 24 and 48 h with a human 3T MRS scanner. see Fig. 1 Conclusions: the spectra of pathological cells treated with NAA and electro stimulation for 60', revealed to be of normal appearance.